Prepared for Counseling: Introducing a Short Scale and Correlates. (2nd October 2019) - Blau, Gary; DiMino, John
Abstract: A new short scale measuring prepared for counseling (PfC) was developed based on 112 nonurgent undergraduates seeking counseling. Having prior counseling, self (vs. other) referral, counselor meeting anxiety, and life satisfaction were significant correlates of PfC. Clients with higher (lower) PfC stopped counseling with (without) discussion.